Green power for African farming: sun, wind and biomass - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Africa's farmers will need increasing supplies of energy if agriculture is to meet the demands of the 21st century. But energy is already a scarce commodity. Although there will always be some reliance on petroleum products, this disparity between...